MENTAL TAX ACCOUNTING FRAMEWORK: EXPANDING THE BOUNDARIES OF MENTAL ACCOUNTING IN TAX DECISION-MAKING - Dwi Rahayu; Heriansyah, Dasep; Rohayati, Iis (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study highlights the role of Mental Tax Accounting in shaping tax compliance in Indonesia, where national revenue largely depends on tax collection. The main issue addressed is the low level of tax compliance, which is not only caused by economic factors but also influenced by psychological aspects, such as how taxpayers mentally process tax-related information. This study aims to develop a Mental Tax Accounting framework by integrating the concepts of mental accounting, cognitive biases, and social factors within the taxation context. This study uses a systematic literature review of 25 selected studies from the Scopus, Web of Science, and Google Scholar databases. The findings identified eight key indicators: (1) mental tax categorisation, (2) cognitive biases, (3) fairness perception, (4) decision heuristics, (5) loss aversion, (6) mental framing, (7) emotional factors, and (8) social influence. The results indicate that behavioral economics-based interventions, such as tax communication redesign, system simplification, and the use of social norms, can serve as additional indicators for tax compliance compared to conventional approaches. Keywords: behavioral economics, tax policy, tax compliance, mental tax accounting, fiscal psychology